Pengaruh Minat Konsumen dan Persepsi Mengenai Sustainable Fashion Terhadap Keputusan Pembelian di Depok Thrift Market Tahun 2023 - Fadhillah, Ilham; Sari, Maemunah Nurmaya; Mashita, Juni (DAS Institute, 2025)
This study aims to determine the influence of consumer interest, the influence of perception of sustainable fashion, as well as the simultaneous influence of consumer interest and perception of sustainable fashion on purchase decisions in Depok Thrift Market. This research is quantitative research using a survey method and using a questionnaire as a research instrument. The population in this study is consumers who purchase thrift products or used clothes at the Depok Thrift Market. The number of samples in this study is as many as 100 respondents. The sampling technique in this study uses the Non-probability Sampling technique, namely Purposive Sampling. The results of the study also showed that there was a significant partial influence between consumer interest on purchase decisions and between perceptions of sustainable fashion on purchase decisions, as well as a significant simultaneous influence between consumer interest and perception of sustainable fashion on purchase decisions of thrift products in Depok Thrift Market